Improved methods for haemozoin quantification in tissues yield organ-and parasite-specific information in malaria-infected mice - Deroost, Katrien (BioMed Central, 2012)
BACKGROUND: Despite intensive research, malaria remains a major health concern for non-immune residents and travelers in malaria-endemic regions. Efficient adjunctive therapies against life-threatening complications such as severe malarial anaemia, encephalopathy, placental malaria or respiratory problems are still lacking. Therefore, new insights into the pathogenesis of severe malaria are imperative. Haemozoin (Hz) or malaria pigment is produced during intra-erythrocytic parasite replication, released in the circulation after schizont rupture and accumulates inside multiple organs. Many in vitro and ex vivo immunomodulating effects are described for Hz but in vivo data are limited. This study aimed to improve methods for Hz quantification in tissues and to investigate the accumulation of Hz in different organs from mice infected with Plasmodium parasites with a varying degree of virulence. METHODS: An improved method for extraction of Hz from tissues was elaborated and coupled to an optimized, quantitative, microtiter plate-based luminescence assay with a high sensitivity. In addition, a technique for measuring Hz by semi-quantitative densitometry, applicable on transmitted light images, was developed. The methods were applied to measure Hz in various organs of C57BL/6 J mice infected with Plasmodium berghei ANKA, P. berghei NK65 or Plasmodium chabaudi AS. The used statistical methods were the Mann–Whitney U test and Pearsons correlation analysis. RESULTS: Most Hz was detected in livers and spleens, lower levels in lungs and kidneys, whereas sub-nanomolar amounts were observed in brains and hearts from infected mice, irrespectively of the parasite strain used. Furthermore, total Hz contents correlated with peripheral parasitaemia and were significantly higher in mice with a lethal P. berghei ANKA or P. berghei NK65-infection than in mice with a self-resolving P. chabaudi AS-infection, despite similar peripheral parasitaemia levels. CONCLUSIONS: The developed techniques were useful to quantify Hz in different organs with a high reproducibility and sensitivity. An organ-specific Hz deposition pattern was found and was independent of the parasite strain used. Highest Hz levels were identified in mice infected with lethal parasite strains suggesting that Hz accumulation in tissues is associated with malaria-related mortality.